Hepatotoxicity and Its Impact on Mortality in COVID-19 Patients : Hepatotoxicty in COVID-19 - Güzel, Efraim; Baydar Toprak, Oya; Aydin, Kaniye (Scientific Reports in Medicine, 2024)
Objective: "COVID-19-related liver damage" can occur frequently in course of COVID-19 disease and cause significant problems. Our study aimed to investigate prevalence of liver damage due to COVID-19, its risk variables, and the effect of liver damage on course of COVID-19 and mortality. Method: One hundred patients over eighteen years of age who were hospitalized between 01.08.2021-01.03.2022 and had positive RT-PCR tests were included in our study. Impaired liver function tests were identified as having alanine aminotransferase(ALT) and aspartate aminotransferase(AST) levels exceeding upper laboratory limits. Results: The mean age of patients included in study was 57.9 ± 14.9 years, with 49% of them being male. In our study, we had an 8% death rate and 37% of patients had abnormal liver function tests. The presence of severe disease(p<0.001), anorexia symptoms(p=0.027), and abdominal pain(p=0.010) were significant for mortality. A prolonged hospital stay was significantly associated with death(p=0.029), with the mean length of hospital stay being 11.8 ± 4.6 days. Favipiravir use for longer than five days was associated with a substantial risk of liver damage(p=0.044) and mortality(p=0.020), while use of antibiotics in carbapenem group was associated with a significant risk of death(p=0.001). Conclusions: It is noteworthy that a considerable proportion of COVID-19 patients may exhibit increased liver tests, which could serve as a significant predictor and risk factor, particularly with regard to mortality. In order to properly monitor and manage COVID-19 patients, particularly those who are at risk, comprehensive measurements, including liver tests, should be carried out on a regular basis.